2019
DOI: 10.2147/ott.s200818
|View full text |Cite
|
Sign up to set email alerts
|

<p>The impact of adjuvant radiotherapy on molecular prognostic markers in gliomas</p>

Abstract: Purpose Changes in MGMT promoter methylation, IDH1 and IDH2 mutation, and 1p/19q co-deletion status in gliomas between first and subsequent resections and their associated clinical factors are poorly described. In this study, we assayed these biomarkers in the clinical setting. Patients and methods We used multiplex ligation-dependent probe amplification to measure MGMT … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 39 publications
(53 reference statements)
0
12
0
Order By: Relevance
“…A couple of them were anecdotal or incidental because they had their main focus on other topics [39][40][41][42][43][44]. Others investigated larger patient cohorts to evaluate, whether the re-determination of the MGMT-methylation status in the relapse situation might be of clinical relevance [36,[45][46][47][48][49][50][51][52][53][54]. Different methods for measuring MGMT methylation and diverse selection criteria have been utilized in these reports ( Table 2).…”
Section: Rationale and Methodologymentioning
confidence: 99%
See 2 more Smart Citations
“…A couple of them were anecdotal or incidental because they had their main focus on other topics [39][40][41][42][43][44]. Others investigated larger patient cohorts to evaluate, whether the re-determination of the MGMT-methylation status in the relapse situation might be of clinical relevance [36,[45][46][47][48][49][50][51][52][53][54]. Different methods for measuring MGMT methylation and diverse selection criteria have been utilized in these reports ( Table 2).…”
Section: Rationale and Methodologymentioning
confidence: 99%
“…The most recent publication on this topic reports patients with astrocytic tumors of different WHO grading [53]. Thus, 12 changes in MGMT promoter methylation status could be observed by MS-MLPA.…”
Section: Systematic Clinical Studies On Mgmt Promoter Methylation Chamentioning
confidence: 99%
See 1 more Smart Citation
“…With regards to clinical heterogeneity, only 20.5% (9/44) of our enrolled articles mentioned the presence or absence of preoperative treatment [38,40,41,45,47,50,53,55]. Some studies suggested that both radiotherapy and chemotherapy can alter a patient's DNA methylation status; therefore, the type of preoperative treatment performed should be clari ed [83,84]. Moreover, four studies investigated the relationship between RASSF1A hypermethylation in peripheral blood and the risk of HCC, and the diagnosis of HCC was con rmed by imaging techniques and serum AFP levels, rather than through pathological examination [56][57][58][59].…”
Section: Discussionmentioning
confidence: 99%
“…Glioblastoma (GBM) is the most malignant type of glioma, characterized by a high level of infiltration, therapeutic resistance, and poor prognosis with a modest median survival of 14.2 months, even under radiation plus temozolomide therapy (1). Genetic changes, including isocitrate dehydrogenase (IDH) 1/2 mutation, 1p/19q codeletion, and O 6 -methylguanine-DNA methyltransferase (MGMT) promoter methylation have recently been accepted as crucial molecular characteristics for prognosis prediction and subgroup stratification (2)(3)(4). Besides these genetic modifications, overexpression of oncogenic protein-coding genes and non-coding RNAs (ncRNAs) (5) and dysregulated posttranslational modification (6) can also modulate the malignant phenotype of glioma.…”
Section: Introductionmentioning
confidence: 99%